Ranid Herpesvirus 3 and Proliferative Dermatitis in Free-Ranging Wild Common Frogs (Rana Temporaria). (July 2017) - Origgi, F. C.; Schmidt, B. R.; Lohmann, P.; Otten, P.; Akdesir, E.; Gaschen, V.; Aguilar-Bultet, L.; Wahli, T.; Sattler, U.; Stoffel, M. H.
Amphibian pathogens are of current interest as contributors to the global decline of amphibians. However, compared with chytrid fungi and ranaviruses, herpesviruses have received relatively little attention. Two ranid herpesviruses have been described: namely, Ranid herpesvirus 1 (RHV1) and Ranid herpesvirus 2 (RHV2). This article describes the discovery and partial characterization of a novel virus tentatively named Ranid herpesvirus 3 (RHV3), a candidate member of the genus Batrachovirus in the family Alloherpesviridae . RHV3 infection in wild common frogs (Rana temporaria) was associated with severe multifocal epidermal hyperplasia, dermal edema, a minor inflammatory response, and variable mucous gland degeneration. Intranuclear inclusions were numerous in the affected epidermis together with unique extracellular aggregates of herpesvirus-like particles. The RHV3-associated skin disease has features similar to those of a condition recognized in European frogs for the last 20 years and whose cause has remained elusive. The genome of RHV3 shares most of the features of the Alloherpesviruses . The characterization of this presumptive pathogen may be of value for amphibian conservation and for a better understanding of the biology of Alloherpesviruses .